Corporate social responsibility and a drag racing attempt in combatting unlawful street racing - Syarizal Abdul Rahim; Norailis Ab. Wahab; Razli Che Razak; Azira Hanani Ab. Rahman (Journal of Economics, Business and Management, 2017)
In current business environment, corporate social responsibility (CSR) has become the powerful source for competitive advantage and it became popular among companies to uphold the image and contribute to the success of the organization. This paper intends to investigate how CSR can help in reducing social issues by conducting a drag racing known as Sprint Test. This study is based on information gathered thru questionnaires distributed to racers at the race event. In depth interviews with a business owners and local enforcement officer was conducted to clarify the effect of the race event to local community. The importance of CSR as seen through the prism of how social issue such as illegal racing can be reduced and eliminated by having a proper race circuit was established in this study.